Les migrants de Beyrouth - Agnès Deboulet; Marie-Antoinette Hily (EchoGéo)
Since the end of the war, in 1990, unqualified, mostly feminine, workers have been massively entering Lebanon. Whether they have regular registration or not, non-Arab, so-called ‘temporary’, or ‘transit’ migrants have entered the labour market, but some of them have been there for about ten years. Many try to join the mixed, full of conflicts environment of peripheral districts, in which it is easier to find housing. Using fieldwork they have been conducting in the Borj-Hamoud suburb, in the east of Beirut, and Jnah and Ouzaï, in the south, the authors describe migratory situations which, although they cannot be applied generally, are nevertheless a good example of the place held by these immigrant